The potential of social media in the classroom in case of scarce resources: Students’ perspectives - Nizonkiza, Deogratias (Stellenbosch Papers in Linguistics Plus, 2023)
In a digital age, the question of using social media in the classroom has sparked interests from both researchers and all those involved in education across the globe. While using technology in the classroom and related benefits are unquestionable in developed countries (Klopfer, Osterweil, Groff and Haas 2009), they are less obvious in developing countries. The present study explores the potential of using social media even in case of scarce resources. Results obtained by means of a questionnaire designed to this end and administered to higher education students at a university in Burundi show that students know the widely used social media, which they use in their everyday life activities. Students consider them excellent vehicles for improving their language skills in both English and French. In regards with incorporating social media into the classroom, students are very positive even though they are aware of the challenges this may pose. Based on the results, this study reflects on the potential of social media in the classroom even with scarce resources.